2022
DOI: 10.1088/1742-6596/2224/1/012118
|View full text |Cite
|
Sign up to set email alerts
|

Smart Dome 4.0: Low-Cost, Independent, Automated Energy System for Agricultural Purposes enabled by Machine Learning

Abstract: Many economically essential crops in Indonesia (such as coffee, tea, chocolate, or copra) require storage or drying under certain environmental conditions, especially temperature and humidity. The solar dryer dome, typically used for agricultural purposes in Indonesia, produces a sufficient amount of heat to increase the evaporation rate inside the dome and reduce the moisture content of the commodity. A hybrid solar dryer accompanied by a photovoltaic panel, fan, and ventilation system is generally suitable. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…These differences in conditions are needed to see the effects caused when the system is used in conditions of high air humidity. As the preliminary study for IoT, ML, and AI implementation in the smart solar dome, researcher had conducted further research, which can be found in [22]. Specifically, this study highlights the implementation and activation of industry 4.0 technology in one of the developed smart solar dryer in Pupuan Bali to encourage more research on smart solar dryer dome, particularly in Indonesia Figure 2.…”
Section: Implementation Of Solar Dryer With Industry 40 Technology In...mentioning
confidence: 97%
See 1 more Smart Citation
“…These differences in conditions are needed to see the effects caused when the system is used in conditions of high air humidity. As the preliminary study for IoT, ML, and AI implementation in the smart solar dome, researcher had conducted further research, which can be found in [22]. Specifically, this study highlights the implementation and activation of industry 4.0 technology in one of the developed smart solar dryer in Pupuan Bali to encourage more research on smart solar dryer dome, particularly in Indonesia Figure 2.…”
Section: Implementation Of Solar Dryer With Industry 40 Technology In...mentioning
confidence: 97%
“…MPPT is a charging controller combined to solar dryer battery unit that maximize the energy extraction from the solar even in a vary sunlight condition. As the result, battery will be charge in the highest power transfer and be able to supply enough energy for the developed smart solar dome, especially at night [22].…”
Section: Figure 3 Arduino Control Box Usage Statusmentioning
confidence: 99%
“…The input gate in LSTM is computed as in equation (2), where the result of the input gate is symbolized as 𝑖 (𝑡) . From Equation 2, 𝑥 (𝑡) , 𝑦 (𝑡−1) , and 𝑐 (𝑡−1) are the entered data, cell value from the last iteration, and output data from the last repetitive calculation respectively with 𝑊 𝑖 , 𝑅 𝑖 , and 𝑝 𝑖 as the weight value.…”
Section: Long Short-term Memorymentioning
confidence: 99%
“…In 2018, the Food and Agriculture Organization of the United Nations (FAO) attempted to avoid the future world's hunger crisis with the motto "No Food Loss and Food Waste" [1]. The developments of some technologies, such as Artificial Intelligence (AI), cloud computing systems, and the Internet of Things (IoT), impacted the change in the agriculture industry in Indonesia, which was supported by the Indonesian Agriculture Ministry by promoting Agriculture 4.0 [2]. The Solar Dryer Dome (SDD) is a part of the Agriculture 4.0 programs that can support farmers in evaporating their agricultural commodities for sustainability or food processing.…”
Section: Introductionmentioning
confidence: 99%